Leptin receptor rs1137101 polymorphism and altered leptin-sOb-R axis contribute to type 2 diabetes risk in Gujarat population - Parmar, Nishant; Rathwa, Nirali; Patel, Roma; Pramanik Palit, Sayantani; Patel, Naisargi; Shetty, Satyashree; Dwivedi, Mitesh; Begum, Rasheedunnisa; Ramachandran, A.V. (Frontiers in Endocrinology, 2026)
Background & aimLeptin (LEP), a pro-inflammatory adipokine secreted by adipocytes acting through leptin receptor (LEPR), is critical in maintaining body weight, lipid and glucose metabolism. LEP and LEPR genetic variants are reportedly associated with type 2 diabetes (T2D). Among these, the LEPR rs1137101 A/G polymorphism has emerged as a potential determinant of metabolic risk. The current study investigates the association of LEP and LEPR genetic variants, along with their transcript and protein levels, and evaluates genotype-phenotype correlations with metabolic parameters and T2D susceptibility in the Gujarat population.MethodsGenomic DNA isolated from PBMCs of 451 controls and 439 patients was used for genotyping LEP (rs7799039 G/A; rs2167270 G/A) and LEPR (rs1137101 A/G; rs1805094 G/C) polymorphisms by PCR-RFLP. RNA isolated from PBMCs was used to assess LEP and LEPR transcript levels by qPCR. Fasting Blood Glucose (FBG) levels, Body Mass Index (BMI) and plasma lipid profile were also assessed for the genotype-phenotype correlation analysis. ELISA was performed to estimate plasma protein levels of leptin and its soluble receptor (sOb-R).ResultsOur findings suggest a significant association of LEPR rs1137101 A/G with T2D, where the GG genotype and G allele conferred a 1.66- and 1.24-fold increased risk for the disease, respectively. The GG genotype also showed an association with increased FBG and TC levels. In addition, an increased GG haplotype frequency, increased LEP transcript and protein levels, and decreased LEPR transcript and protein levels were observed in T2D patients. Moreover, leptin protein levels showed a positive correlation with increased BMI and TG, while sOb-R protein levels showed a positive correlation with increased BMI, FBG, and TG levels.ConclusionThe LEPR rs1137101 A/G polymorphism, together with elevated leptin, and decreased sOb-R protein levels, may increase susceptibility to T2D in the Gujarat population.